Standardization of the oil extraction process of Mauritia flexuosa from Guaviare, Colombia. - Acosta Chinchilla, Jasbleidy Marcela; Acosta Rodriguez, Gustavo Adolfo; Arias, Juan Pablo (Revista Colombiana de Investigaciones Agroindustriales, 2021)
Maurita flexuosa is a dioecious palm and its fruit is an oily drupe of which about 16.58% of the mesocarp can be used for the process of transformation and extraction of oil, due to its high oleic acid index, of which its content of provitamins and polyunsaturated oils that contribute to its antioxidant activity. In order to determine the natural supply of Mauritia flexuosa in the municipality of San José del Guaviare, population studies were carried out using GIS and ArcGIS tools. The existing natural offer in the municipality corresponds to 1,351,175 palms in production and an estimated 140,977 tons of drupes ready for use. For the extraction of the oil, Soxhlet, Folch methods and cold pressing were evaluated, obtaining a maximum yield of 51%, 13.35% and 28.63%, respectively. The experimental model called 2K was used, with 16 trials where the effect of temperature, weight and pH was defined. Likewise, aspects of the market, costs, extraction processes and legislation were considered. Finally, the content of bioactives was verified by chromatography.